Journey to euphoria - Izayati Mustaffa 1968- (Eiza Brainwork Publishing House, 2021)
From the depths of great loss and pain, a woman struggles to keep her family intact. Facing seemingly insurmountable challenges and hardships upon the death of her beloved husband, she crosses the chasm from being the pampered wife to an industry driver. Letting go of the person she used to be, realising that her once zone of comfort could no longer help her, she rises like a phoenix to conquer her demons of self-doubt, fear and inertia. Along the way, she discovers many like her, women who were struggling to survive, living without love and support, and facing deep depression. And along the way towards reinventing herself, she discovers the wonderment of small successes and joys, spurring her on to reach the height of achievements and the desire to reach out to all women who want to become the best of themselves.